Infuence of the financial and economic crisis on the development of macroeconomic parameters of economies in the Czech Republic, Slovakia and Austria since 2008 till 2015 - Pavelka, Ľuboš, 1962-
Porovnanie primeraného hrubého domáceho produktu pred a po kríze vo vybraných krajinách.